Medical students as interpreters in health care situations: "… it's a grey area". Issue 4 (12th June 2019) - Ryan, Anna Therese; Fisher, Caleb; Chiavaroli, Neville
Abstract: Objective: To examine the extent to which medical students in Australia are acting as interpreters in medical settings, and their perceptions of this activity. Design, setting, participants: Anonymous online survey of final year students in the graduate medical program of the University of Melbourne, undertaken in 2014. Main outcome measures: Numbers of students who had acted or who had been asked to act as ad hoc interpreters in health care situations during their clinical rotations and outside the medical education context. Results: 146 of 319 final year medical students completed the survey (46% response). 106 students (73%) reported they could speak at least one language in addition to English; none had formal interpreting qualifications, but 40 (36%) had been asked to interpret during clinical rotations, and 36 (34%) had done so. The students described a diverse range of experiences, including complex interactions regarding informed consent and the breaking of bad news. Conclusion: Medical students frequently acted as interpreters during their clinical training. Most did not feel appropriately qualified to interpret in clinical situations, and some felt pressured to do so, but many found the experience positive. Our study highlights the lack of clear guidelines regarding medical student interpreters in Australian health care settings.